Penyuluhan Pembuatan Parfum dari Minyak Atsiri Daun Kayu Manis di SMAIT Insan Cendekia Jayapura - Johnson Siallagan; Lodwyk N. Krimadi; Diana M. Abulais; Martha K. Sefa; Demas R. Yaam (JURNAL PENGABDIAN PAPUA, 2025)
Cinnamomum burmannii is a leading Indonesian commodity in global trade. The part of the cinnamon plant that has not been fully utilized is the leaves. Cinnamon leaves can be used as a prospective product, namely essential oils that can be used as base notes in making perfume. Essential oil processing can be done simply by the steam distillation method. However, many people still do not know how to process essential oils properly. This Community Service (PKM) activity is a form of knowledge transfer by the implementing team from the Chemistry Department of Cenderawasih University to students of SMAIT Insan Cendikia Jayapura regarding the manufacture of perfume from essential oils made from cinnamon leaves. The activity was carried out on June 4, 2025. The methods used in this service included an initial survey, implementation of activities including counseling and demonstrations, and activity evaluation. During this activity, a simple distillation unit was also handed over to the school, as a provision for students to practice the material that had been given in the hope of improving students' skills in processing essential oils. The results achieved in this activity showed that students were very enthusiastic, active, and interactive in absorbing knowledge. Based on the evaluation results (initial test and final test) showed a significant increase to 93% after participating in this activity.